2022
DOI: 10.3390/ijerph192013176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Outcomes of Abdominal Radical Hysterectomy and Total Laparoscopic Radical Hysterectomy for Cervical Cancer: A Retrospective Analysis of Data Collected before the LACC Trial

Abstract: Although a surgical approach is one of the key treatments for stages IA1-IIA2, results of the Laparoscopic Approach to Cervical Cancer (LACC) published in 2018 radically changed the field, since minimally invasive surgery was associated with a four-fold higher rate of recurrence and a six-fold higher rate of all-cause death compared to an open approach. We aimed to evaluate surgical outcomes of abdominal radical hysterectomy (ARH) and total laparoscopic radical hysterectomy (TLRH) for cervical cancer, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Different approaches for hysterectomy include abdominal hysterectomy where the uterus and cervix are removed from a large abdominal incision, and laparoscopic hysterectomy where small instruments and a camera is inserted into the abdomen through small incisions. Although the latter choice is less invasive and may in turn cause less complications, recent research shows a higher recurrence rate for laparoscopic hysterectomy [ 32 ]. Radical trachelectomy is a primary method of treatment for patients with early-stage cervical cancer [ 33 ] and is considered an option where the patient’s fertility is protected by removing the cervix, small part of upper vagina and parametria but leaving the uterus intact.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches for hysterectomy include abdominal hysterectomy where the uterus and cervix are removed from a large abdominal incision, and laparoscopic hysterectomy where small instruments and a camera is inserted into the abdomen through small incisions. Although the latter choice is less invasive and may in turn cause less complications, recent research shows a higher recurrence rate for laparoscopic hysterectomy [ 32 ]. Radical trachelectomy is a primary method of treatment for patients with early-stage cervical cancer [ 33 ] and is considered an option where the patient’s fertility is protected by removing the cervix, small part of upper vagina and parametria but leaving the uterus intact.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of vNOTES may open new possible scenarios also for the treatment of malignant gynecological diseases [24]. Indeed, the Laparoscopic Approach to Cervical Cancer (LACC) trial found worse oncological outcomes in women with cervical cancer undergoing laparoscopic surgery compared with open surgery, and this raised concerns about the use of MIS for this purpose and led to an ongoing debate [25,26]. From this perspective, further studies should be aimed to investigate the role of vNOTES for gynecological cancers, in order to clarify whether this technique has similar surgical and oncological outcomes compared with other approaches [27][28][29][30][31][32][33].…”
Section: Overall Results Summarymentioning
confidence: 99%
“…ARH therefore has re-emerged as a mainstream treatment for cervical cancer, bringing attention to the effect of abdominal surgeon volume on the complication rates. Despite the finding of poor survival with minimally invasive surgery (MIS) in LACC trail, some studies were still conducted to re-establish the role of MIS and select the appropriate patient for MIS, considering the tumour size and the histological type [32][33][34][35]. Thus, further exploration of the effect of surgeon volume on complications among patients who undergo LRH is also warranted.…”
Section: Discussionmentioning
confidence: 99%